Cost-benefit analysis for health project evaluation (example of a Russian outpatient clinics' project in the Novosibirsk region) - Tatyana Novikova; Tatyana Novikova; Maria Kaneva; Mokhidilkhon Zafarjonova (Frontiers Media S.A., 2023)
IntroductionThe development of social infrastructure projects in medicine corresponds to transforming public priorities toward social development in general and health care in particular. Therefore, there is a need to develop comprehensive quantitative methods for evaluating such projects.MethodsThis paper uses a combination of two approaches: first, cost-benefit analysis taking into account the relationship between financial and economic efficiency; second, the study of the efficiency of participation in a public-private partnership concerning project efficiency. The model's financial bloc is focused on analyzing the return on investment in fixed and working capital, considering the terminal value. The economic bloc includes social and tax effects (along with environmental, price, indirect, and other specific public effects). We apply fixed effects regression models to calculate multipliers used to estimate the social effects. Multipliers are based on: public health expenditure, human development index, and life expectancy. The proposed methodology has been adapted for evaluating the Seven Polyclinics' project as a flagship project for developing social infrastructure in the Novosibirsk Region.Results and discussionThe evaluation results revealed a deficient level of financial efficiency of the project characterized by negative net present value and low internal rate of return. Simultaneously, the efficiency of participation in the project for private investors using the public-private partnership mechanism is characterized by high rates of return on private investment. In the transition to the economic analysis, the results fundamentally change, taking into account social and tax effects and detecting an exceptionally high level of all economic indicators of the project. As the project's primary beneficiaries, the economic analysis identified polyclinic patients who received the opportunity to acquire new medical services. At the same time, within the financial analysis framework, the mechanisms for implementing the project were determined, ensuring the consistency of interests. The distribution of effects among the project participants was compared for various funding methods, including the public-private partnerships mechanism. It is shown that the project implementation leads to significant social effects and provides a noticeable improvement in population health. The proposed methodology can be used for decision making on the implementation of similar projects.